A role of Pygopus as an anti-repressor in facilitating Wnt-dependent transcription. - Mieszczanek, J.; de la Roche, M.; Bienz, M. (Proceedings of the National Academy of Sciences of the United States of America, 2008)
Wnt/beta-catenin signaling controls animal development and tissue homeostasis, and is also an important cancer pathway. Pygopus (Pygo) is a conserved nuclear Wnt signaling component that is essential for Wingless-induced transcription throughout Drosophila development. It associates with Armadillo/beta-catenin and T cell factor (TCF) through the Legless/BCL9 adaptor, but its molecular function in TCF-mediated transcription is unknown. Here, we use a groucho-null allele to show that Groucho represses Wingless target genes during Drosophila development. Interestingly, groucho pygo double-mutants revealed that Pygo is not obligatory for transcriptional and phenotypic Wingless signaling outputs if the interaction between Groucho and Drosophila TCF is compromised genetically. Pygo function is also non-essential for Wingless outputs in the absence of other transcriptional antagonists of Wingless signaling. This indicates an anti-repressor function of Pygo: we propose that Pygo predisposes Drosophila TCF target genes for rapid Wingless-induced transcription, or that it protects them against premature shut-down.